Herniation of gravid uterus in a ewe - SREENU, MAKKENA; SRINIVAS, MANDA; RANI, N LAKSHMI (The Indian Journal of Animal Reproduction, 2007)
A case of herniation of gravid uterus in an ewe was reported and the hemiorrhaphy to treat it was discussed.